Application of Electrocardiogram Localization during Peripherally Inserted Central Catheter Line Insertion into the Persistent Left Superior Vena Cava of Neonates - Wu, Liyuan; Wan, Lijia; Peng, Min; Cao, Tian; Wang, Qin; He, Xiaori (American Journal of Perinatology, 2021)
Background Most neonates with persistent left superior vena cava (PLSVC) have no clinical symptoms or hemodynamic changes, and this anomaly is only found during cardiac catheterization, pacemaker implantation, or central venous catheterization. Electrocardiogram (ECG) localization is helpful for the application of the peripherally inserted central catheter (PICC) technique in neonates with PLSVC.Objective To explore the characteristic waveforms of the P wave when a PICC under ECG localization is applied in neonates with PLSVC.Study Design The observation and management strategies for the P wave changes during catheter insertion (CI) of two neonates with PLSVC admitted to our institution between January and July 2020, who underwent PICC line insertion, were summarized.Results The characteristic P wave changes in two children with a PICC line inserted via the PLSVC were observed. When a wide inverted P wave appeared on ECG, the catheter was immediately withdrawn by 0.5 cm, a bidirectional P wave gradually appeared and then disappeared. After that, the catheter was further withdrawn by 0.5 cm. After catheterization, the optimal position of the PICC was confirmed by X-ray photography and bedside B-ultrasound. The PICC line was removed as scheduled after indwelling for 18 and 29 days, respectively, in the two cases, and no PICC-related complications occurred during indwelling.Conclusion The characteristic P wave changes on ECG during CI provide important clinical reference values for the application of the PICC technique under ECG localization in neonates with PLSVC.Key Points
Keywords: electrocardiogram localization; persistent left superior vena cava; peripherally inserted central catheter; neonate